Enhancing Mobile Library App User Experience Using HCD and Usability Metrics - Siahaan, Ranty Deviana; Sitopu, Tesalonika Aprisda; Marbun, Tabitha Aquila; Bukit, Gerry Benyamin (Journal of Information Systems and Informatics, 2025)
This study analyzes the improvement of usability metrics and the correlation between usability variables and user experience in the development of a mobile-based digital library application. Using the Human-Centered Design (HCD) approach, the study employed Concurrent Think Aloud (CTA) and Post-Study System Usability Questionnaire (PSSUQ) for usability evaluation. The focus was on four main usability metrics: effectiveness, efficiency, satisfaction, and learnability. The study involved 100 respondents from IT Del students. The results showed significant improvements in all usability metrics: effectiveness increased from 88% to 100%, efficiency rose from 0.087 to 0.148 goals/second, satisfaction improved from 82.05% to 87.05%, and learnability improved with the number of failed tasks reducing from four to zero. Multiple linear regression analysis revealed a strong positive correlation between usability metrics and user experience, with an R² value of 0.665, meaning 66.5% of the variation in user experience can be explained by the usability metrics. All usability metrics positively contributed to improving user experience. These findings confirm that applying HCD and systematic usability evaluation can significantly enhance the quality of digital applications, particularly for mobile-based libraries, and offer valuable insights for the design of digital library apps in higher education contexts.